2016
DOI: 10.5897/ajb2016.15509
|View full text |Cite
|
Sign up to set email alerts
|

Production of extracellular laccase from the newly isolated Bacillus sp. PK4

Abstract: Laccase belongs to the family of multicopper oxidase and have wide range of biotechnological applications starting from the food industry to bioremediation. However, the use of laccase at commercial scale is hindered by factors like high enzyme cost, low activity and /or stability under given conditions. This study was carried out with aim of screening for extracellular thermostable laccase producing bacteria. Twenty-two (22) laccase positive strains were isolated from the selected environmental samples while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…As pH increase to 7.0, 7.5 and rising toward alkalinity there was gradual increase of lignin degradation and biomass production. This is similar with the finding of Murugesan and Vembu [18] who reported that Bacillus sp. produced high laccase activity at pH 7.5 and gradually decrease from 7.5 to 10.0.…”
Section: Pseudomonas Aeruginosasupporting
confidence: 93%
See 2 more Smart Citations
“…As pH increase to 7.0, 7.5 and rising toward alkalinity there was gradual increase of lignin degradation and biomass production. This is similar with the finding of Murugesan and Vembu [18] who reported that Bacillus sp. produced high laccase activity at pH 7.5 and gradually decrease from 7.5 to 10.0.…”
Section: Pseudomonas Aeruginosasupporting
confidence: 93%
“…The effect of growth parameters were determined as in one factor one time method as described by Murugesan and Vembu [18] A twenty four (48) hours old culture of Pseudomonas aeruginosa was inoculated into 50 ml of mineral salt medium (MSA) incorporated with 5% lignin extract from plant. The growth conditions such as incubation time, temperature, pH and agitation whose show highest activity were chosen and used in this study.…”
Section: Effect Of Some Growth Parameters On Crude Lignin Degradation and Bacterial Biomass Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of variables for growth and production of laccase. The physical parameters, for example,pH (2-10), temperature (20-55˚C), incubation time (1-12 d) [24], and nutrients, such as carbon sources (1.5%),which included glucose, sucrose, starch, maltose, lactose, fructose, and glycerol, organic nitrogen sources (1.5%), such as L-asparagine, glutamic acid, glycine, L-proline, yeast extract, peptone, urea, inorganic nitrogen sources (1.5%),which includedammonium nitrate, sodium nitrate, potassium nitrate, ammonium chloride, ammonium dihydrogen phosphate, and ammonium sulfate, inducers (10-50 μM), namely CuSO 4 , tween 80, veratryl alcohol, guaiacol, 2,5 xylidine, vanillic acid, gallic acid, ammonium tartrate, and vanillin were optimized forthemaximumproduction of laccase [30].…”
Section: Optimization Experimentsmentioning
confidence: 99%
“…The physical parameters viz. pH (2)(3)(4)(5)(6)(7)(8)(9)(10), temperature (20- were optimized for optimum production of laccase [30].…”
Section: Optimization Of Variables For Growth and Laccase Productionmentioning
confidence: 99%